The Photosynthesis, Na+/K+ Homeostasis and Osmotic Adjustment of Atriplex canescens in Response to Salinity - Pan, Ya-Qing; Guo, Huan; Wang, Suo-Min; Zhao, Bingyu; Zhang, Jin-Lin; Ma, Qing; Yin, Hong-Ju; Bao, Ai-Ke (Frontiers in Plant Science, 2016)
Atriplex canescens (fourwing saltbush) is a C4 perennial fodder shrub with excellent resistance to salinity. However, the mechanisms underlying the salt tolerance in Atriplex canescens are poorly understood. In this study, 5-week-old A. canescens seedlings were treated with various concentrations of external NaCl (0-400 mM). The results showed that the growth of A. canescens seedlings was significantly stimulated by moderate salinity (100 mM NaCl) and unaffected by high salinity (200 or 400 mM NaCl). Furthermore, A. canescens seedlings showed higher photosynthetic capacity under NaCl treatments (except for 100 mM NaCl treament) with significant increases in net photosynthetic rate and water use efficiency. Under saline conditions, the A. canescens seedlings accumulated more Na+ in either plant tissues or salt bladders, and also retained relatively constant K+ in leaf tissues and bladders by enhancing the selective transport capacity for K+ over Na+ (ST value) from stem to leaf and from leaf to bladder. External NaCl treatments on A. canescens seedlings had no adverse impact on leaf relative water content, and this resulted from lower leaf osmotic potential under the salinity conditions. The contribution of Na+ to the leaf osmotic potential (Ψs) was sharply enhanced from 2% in control plants to 49% in plants subjected to 400 mM NaCl. However, the contribution of K+ to Ψs showed a significant decrease from 34% (control) to 9% under 400 mM NaCl. Interestingly, concentrations of betaine and free proline showed significant increase in the leaves of A. canescens seedlings, these compatible solutes presented up to 12% of contribution to Ψs under high salinity. These findings suggest that, under saline environments, A. canescens is able to enhance photosynthetic capacity, increase Na+ accumulation in tissues and salt bladders, maintain relative K+ homeostasis in leaves, and use inorganic ions and compatible solutes for osmotic adjustment which may contribute to the improvement of water status in plant.